قياس أثر التضخم وال نفاق العام على النمو الاقتصادي (2019/1980 ) في الجزائر - بن بوزيد عبد الرحمن (جامعة البليدة2؛كلية العلوم الاقتصادية العلوم التجارية وعلوم التسيير, 2024)
تطرقنا في ھذه الأطروحة إلى النظريا ت المفسرة لمفھوم الإنفاق العام والتضخم وإلى النظريا ت المفسرة للنمو ووقفنا على أھمية المقاربات الحدیثة لمفھوم النمو مع التركي زعل ى مصادر النمو الاقتصادي ومحدداته، خاصة ما يصطلح عليه بالنماذج الحدیثة للنمو الاقتصادي، كما حاولنا تفسير العلاقة بين معدلي التضخم والإنفاق العام والنمو الاقتصادي؛ ھدفنا الأساسي في ھذه الدارسة ھو إيجاد العلاقة المباشرة بين النمو ومعدلي التضخم والإنفاق العام في الجازئر، لبناء والوقوف على مختلف السياسات الاقتصادية ومساهمتها ، نموذج یتوافق مع واقع الاقتصاد الجزائري حي ث تم استخدام منهجية الانحدار الذاتي للفجوات ،(2019 /1980 ) في صنع النمو خلال الفتر ة كأحد تطبيقات القياس الاقتصادي ، وتوصلت الدارسة وجود سببية من ARDL الزمنية الموزعة الإنفاق العام ومعدلات التضخم كمتغيارت تفسيرية والناتج الداخلي الخام كمتغير تابع، مع إمكانية وجود تقارب بين متغيارت الدارسة في المدى الطويل. من خلال نماذج تصحيح الخطأ تحصلنا على وجود تأثير في المدى القصير والمدى الطويل في العينة محل الدارس ة 𝐿𝑃𝐼𝐵 نحو معدل لوغاريتم النم و LDP من مؤشر لوغاريتم الإنفاق العام . النمو، ، الكلمات المفتاحية: الإنفاق العام، التضخم . القياسيةARDL الاقتصاد الجزائري ، نماذج This thesis focuses on studying the statistical relationship between inflation rates and public expenditure as independent variables, and economic growth as a dependent variable, using statistical data from Algeria. We addressed the theoretical frameworks explaining the concepts of public expenditure and inflation, as well as theories elucidating growth. We emphasized the significance of modern approaches to understanding growth, focusing on the sources and determinants of economic growth, particularly what is referred to as modern models of economic growth. Additionally, we attempted to interpret the relationship between inflation rates, public expenditure, and economic growth. Our main objective in this study was to establish a direct correlation between growth and the inflation rates and public expenditure in Algeria, in order to develop a model that aligns with the Algerian economic context. We also examined various economic policies and their contributions to shaping growth during the period 1980-2019. The study utilized autoregressive distributed lag (ARDL) models as one of the applications of economic measurement. The research confirms the causal relationship between public expenditure and inflation rates as explanatory variables, and gross domestic product (GDP) as the dependent variable, with the possibility of convergence among the study variables in the long term. Through error correction models, we found evidence of both shortterm and long-term impacts, indicating an influence of the logarithm of public expenditure (LDP) on the logarithm of GDP growth (LPIB) within the studied sample. Keywords: Public expenditure, inflation, growth, Algerian economy, ARDL econometric models .
Keywords: التضخم; النمو